Understanding Post-ACL Injury Osteoarthritis: Pathophysiology and Management Insights - Rathore, Rohit; Pachauri, Drishti; Arya, Vratika; Singh, Ritu; Reetuja, Reetuja; Mudgal, Mukul; Aggarwal, Priyanshi; Maddhesiya, Aditya; Shubhangi, Diksha; Anand, Mohit (Journal of Neonatal Surgery, 2025)
PTOA or post-traumatic osteoarthritis is arising as a result of joint injuries, ACL damage being the most predominant. ACL tears or injuries are prevalent among working individuals of diverse backgrounds. The PTOA after ACL injury develops is associated with mere structure, biology, and mechanical factors, which can also be termed neuromuscular, and altogether disturb the homeostasis of the joint, leading to increased cartilage wastage and smoother equators or erosion. Techniques in surgeries and rehabilitation still the rate of PTOA is extremely high due to many factors more than 50-90 have been observed within a decade. This review helps me understand the mechanisms of PTOA progression, measures for preventing it using ACL reconstruction, ACL-R, and the changes in the method of diagnosis and treatment. The need for early-stage intervention is underscored by multi-PTOA rehabilitation. Strapping the gaps is crucial to decreasing the impact of PTOA, as surgeons improve the lives of people suffering from it.